Wynagrodzenia w kontekście spójności społeczno-ekonomicznej - Cieślak, Iwona (Wydawnictwo Uniwersytetu Rzeszowskiego, 2008)
Płaca zasadnicza zgodna z wartością pracy jest pochodną kapitału ludzkiego pracownika. Zgodność płacy z wartością pracy jest przesłanką spokoju społecznego i sprawiedliwego podziału sumy wytworzonych produktów, jest jednym z kryteriów warunkujących spójność społeczno-ekonomiczną. Teoria kapitału ludzkiego zachęca do stosowania płacy uzależnionej od umiejętności i kompetencji, zakłada, że inwestowanie w ludzi powoduje wzrost ich wartości. Pracownicy mają określoną wartość, którą nabywają i powiększają w wyniku inwestowania w zdobycie dodatkowej wiedzy i kompetencji poprzez szkolenie, rozwój i doświadczenie. Obiektywne ustalanie wielkości płac jest bardzo ważnym czynnikiem motywacyjnym, niwelującym niepożądane rozpiętości płacowe wywołujące odczucia nierówności płacowych i istotnym z punktu widzenia spójności społeczno-ekonomicznej.

In Poland, professional group of doctors are notorious for long-standing campaign for pay rises. Whether this campaign is well grounded or not, may be examined using well known and established models of human and intellectual capital, all based on the assumption that every employee may be assigned the value of their human capital, which can be subject to an exchange relation between the employee and the employer. The principle of equivalence between the salary and the value of labour transferred by the employee to the employer is socially accepted. When working, the employee expends her own energy; and she expects in return a remuneration which shall allow her to supplement this expenditure and maintain her capital. Correct definition of the salary level protects human and intellectual capital from depreciation. Imbalance between the salary and the value of work over a prolonged period of time is bound to lead to the employees’ discontent. An example of a prolonged discontent in Poland is provided in the professional group of doctors.
Wages in the Context of the Socio-Economic Coherency